THE USE OF SILICEOUS ROCKS TO INCREASE THE STRENGTH OF CONSTRUCTION CERAMICS - SUBBOTA, IRYNA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The purpose of the research are physiochemical processes of forming the structure and properties of ceramic masses based on local low-melting clay raw materials of the Kyiv region. Building ceramic materials differ by a combination of properties, such as durability and architectural expressiveness and therefore are one of the main ones in modern construction. With usage of fusible raw materials in production there is a need, along with an increase in volumes, to improve the quality of wall ceramics and expand the range of manufactured products. The reduction of high-quality clay raw materials reserves has led to usage of other sources of raw materials, that might ensure building ceramics production. Attention has been paid to the use of siliceous rocks (cherts, trepels, diatomites) recently, the reserves of which in Ukraine are quite significant, however they are not widely used. Preparation of ceramic materials effectiveness significantly relies on physical and chemical processes of their thermal processing. Drying the semi-finished product process is important for the quality of the finished product and is estimated as 10-12% of total final products cost. Mainly poly-mineral clay compositions with adding of natural mineral raw material are used to manufacture building materials. It is necessary to study their technological properties, to increase the usage effectiveness. Therefore, it is important to study technological properties of masses that are based on fusible clay and usage of mineral rock which contain gaize as an addition. The study presents the research results of mass compositions based on local low-melting clay and the usage of non-deficient siliceous mineral rock as an addition. This allows to expand the use of local natural minerals for efficient and environmentally clean production of building ceramics.